Synthesis of Aragonite from Precipitated Calcium Carbonate: A Pilot Scale Study - Sari, Ellyta; Desmiarti, Reni; Zulhadjri, Zulhadjri; Alif, Matlal Fajri; Rosadi, Maulana Yusup; Arief, Syukri (Universitas Gadjah Mada, 2024)
The CO2 mineralization pathway is considered a promising option for carbon capture usage and storage because the captured CO2 can be permanently stored, and secondly industrial waste (i.e., petrochemical refinery, lime, and cement kiln dust) can be recycled into value-added carbonate materials by controlling the crystal polymorphs and properties of mineral carbonate. This study investigated the CO2 mineralization utilized for the synthesis of precipitated calcium carbonate (PCC) via low temperatures at 30 °C and 55 °C with the addition of 50 and 75 g/L of ammonium chloride (NH4Cl). The pilot scale of PCC production was established to simultaneously produce PCC with low energy demand by reporting the feasibility of economic analysis and to develop the mineral carbonation that can transform limestones and CO2, which was captured from the petrochemical refinery process into economically valuable PCC. It is found that the aragonite phase of PCC can be generated at a room temperature of 30 °C by adjusting the CO2 flow rate. In addition, the use of NH4Cl, which transformed into ammonium carbonate ((NH4)2CO3) during the calcination process, can maintain the stable aragonite phase by varying the NH4Cl concentration.